Implementasi Sistem Informasi Penggajian untuk Meningkatkan Efektivitas Pengelolaan Data di STEI Bina Muda Bandung - Nugraha, Muhamad Fahmi; Maulana, Gilang Angga; Tryana, Anjas (Jurnal Accounting Information System (AIMS), 2025)
The management of payroll data at the Islamic Economics College (STEI) Bina Muda Bandung is still conducted manually, leading to inefficiencies, risks of errors, and delays in administrative processes. This research aims to develop an integrated payroll information system to improve efficiency, accuracy, and transparency in payroll data management. The Scrum method was chosen as the system development approach due to its flexibility, rapid iteration, and focus on team collaboration. The development process was carried out through a series of sprints, with each sprint focusing on completing specific features, such as payroll calculation automation and payslip generation. User feedback (from administrative staff) was collected regularly to ensure the developed system met their needs. The results show that the Scrum method is effective in producing an information system that automates payroll processes, reduces payslip generation time, and improves staff satisfaction. The implementation to serve as a model for other educational institutions in supporting digital transformation. Thus, this research makes a significant contribution to improving the quality of payroll data management in the education sector through a structured and adaptive Scrum approach.